Pharmacological and safety profile of a prolonged-release lanreotide formulation in acromegaly. Issue 12 (2nd December 2021) - Neggers, Sebastian; Badiu, Corin; Biagetti, Betina; Durand-Gasselin, Lucie; Petit, Anne; Petrossians, Patrick; Regnault, Benjamin; Rich, David; Shafigullina, Zulfiya; Shustov, Sergey; Vydrych, Anna
ABSTRACT: Background: Patients with acromegaly require lifelong medication; a longer dosing interval would reduce treatment burden. This study investigated the pharmacokinetics, pharmacodynamics and safety profile of a new prolonged-release formulation (PRF) of lanreotide every 12 weeks. Research design and methods: In this multicenter, open-label, dose-ascending study, cohorts of nine patients with acromegaly received single doses of lanreotide PRF according to a 3 + 3 + 3 scheme in order to determine the maximum tolerated dose (MTD). Following a 12-week treatment period, patients were followed up for a further 12 weeks. Serum lanreotide, insulin-like growth factor-1 and growth hormone concentrations were analyzed. Adverse events were monitored throughout the study. Results: The MTD was not reached. Peak lanreotide serum concentration values were similar in all cohorts, whereas area under the curve values from time zero to 85 days increased but were not dose-proportional. The apparent elimination half-life of lanreotide PRF was approximately 54–63 days, in line with the expected prolonged-release characteristics. Growth hormone and insulin-like growth factor-1 levels were generally stable. Conclusions: The safety and tolerability profile was in-line with the known safety profile of lanreotide autogel. Lanreotide PRF was well tolerated and the pharmacokinetic profile suggests that a dosing interval of 12 weeks could be achievable. Clinical trial registration: www.clinicaltrials.gov identifier is NCT02396953; EudraCT 2014–002389-62.